Profile semantyczne przyjaciela i wroga w polsko-, rosyjsko- i niemieckojęzycznym obrazie świata - Gawarkiewicz, Roman (Studia Rossica Posnaniensia, 2021)
The article aims at reconstructing and comparing the cultural meanings contained in the concepts friend and enemy. To achieve the objective, the author referred to research methodologies elaborated by cognitive linguists. Particularly useful were those approaches which emphasize the necessity of including both the role of cognitive processes in descriptions of language and its historical, cultural and social underpinnings. In such approaches, questionnaires and surveys are accepted as sources of empirical data. In the current study, an analysis of the specific connotations attached to the concepts friend and enemy in Polish, German and Russian is performed. The obtained results allow for creating a hierarchy of the criteria that speakers of the three languages take into consideration, and for establishing significant similarities and differences between the Polish, German and Russian semantic profiles of the two concepts.